Penggunaan Media Puzzle Untuk Meningkatkan Minat Siswa Dalam Pembelajaran Bahasa Arab - Dede Rizal Munir; Naila Ainun Nida; Maftuhah (JURNAL ILMIAH RESEARCH STUDENT, 2023)
This research aims to determine the effect of using puzzle media on increasing students' interest in learning Arabic at MIN 2 Purwakarta. Because this research was motivated by a lack of interest in learning Arabic and because the media and methods used were less attractive to children, the process of learning Arabic was less effective. Next, the media used is puzzle media. This research uses a quantitative approach with an experimental method, a pre-experimental research design with a one group pretest-posttest design type. In this study the population was all students at MIN 2 Purwakarta, and the sample taken consisted of 9 students. Thus, it can be seen from the research results that students are effective, namely by using puzzle media in increasing students' interest in learning Arabic at MIN 2 Purwakarta.